Scorpion Sting in Izeh, Iran: An Epidemiological Study During 2009-2011 - Ne'matollah Maghsood; Babak Vazirianzadeh; Arash Salahshoor (Journal of Basic & Applied Sciences, 2015)
Background:Izeh is one of the counties of Khuzestan province that its people suffer from scorpion sting. So according to the high prevalence of scorpion sting in this area and the lack of a reduce cases of scorpion stings, timely treatment and prevention of mortality and morbidity resulting from this phenomenon using results of the current epidemiological investigation. Methods: This cross-sectional and retrospective study has been conducted based on statistics of scorpion sting of Izeh Health Center during 2009-2011. The data including: age, sex, season and month of stings, location of event (urban or rural), location and time of the sting, the stung organ and scorpion species were collected and recorded in the official forms and transformed into the tables and graphs for presentation. The species of scorpions were recognized using Iranian scorpion key. Results: During 2009 to 2011 a total of 5804 cases of scorpion sting referred to health and medicine centers. Most cases of scorpion sting were females (55.53%). The age range was 15- 24 year olds and the highest incidence rate of scorpion sting was on August. Totally 6 species of scorpions were recognized during the current study and Androctonus crassicaudawas the most frequent spcies which caused the scorpion sting. One of the most important results of the present study was to report Compsobuthus matthienseni as the 2nd dominant scorpion sting cause and Mesobuthus eupeus as the least cause of scorpion sting in the region, in contrast to other parts of Khuzestan which this species has been reported as the most frequent cause of scorpion sting inKhuzestan province. Conclusions:Since there is a large number of cases with a history of previous scorpion stings, it appears we can reduce the incidence of this occurrence using education of preventing and control ways from this phenomenon to persons referred to treatment in the studied area and repeat those in similar regions with high range of scorpion sting. Furthermore with focuse on the educational activities in the warm seasons, when is the peak time of scorpion activity it will be more effective in reducing this phenomenon